Syllable structure the limits of variation - Duanmu, San. (Oxford : Oxford University Press, 2009)
This title looks at the range of possible syllables in human languages. The syllable is a central notion in phonology, but phonologists are divided on even the most elementary issues. San Duanmu explores and clarifies these and many other related issues through an in-depth analysis of entire lexicons of several languages.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Syllable